Induksi Tunas Tanaman Tebu (Saccharum officinarum L.) Varietas CMG Agribun dengan Pemberian Berbagai Konsentrasi Indole Butyric Acid (IBA) dan Benzyl Amino Purine (BAP) - Nurlita Islamia; Sulistyo Sidik Purnomo; Hayatul Rahmi; Sri Suhesti (Peneliti.net, 2022)
The purpose of this research is to obtain the proper concentration of IBA and BAP for the growth and development of sugarcane varieties of CMG Agribun shoots on tissue culture. The research method used is a RAL of factorial patterns and a 5% DMRT advance test with IBA and BAP concentrations. There are 5 repeats and 12 treatment, i.e (BAP 0 + IBA 0), (BAP 0 + IBA 0,3 mg/L), (BAP 0 + IBA 0,5 mg/L), (BAP 0 + IBA 1 mg/L), (BAP 0,3 mg/L + IBA 0), (BAP 0,3 mg/L + IBA 0,3 mg/L), (BAP 0,3 mg/L + IBA 0,5 mg/L), (BAP 0,3 mg/L + IBA 1 mg/L), (BAP 0,5 mg/L + IBA 0), (BAP 0,5 mg/L + IBA 0,3 mg/L), (BAP 0,5 mg/L + IBA 0,5 mg/L), (BAP 0,5 mg/L + IBA 1 mg/L). The results showed that the concentration of BAP and IBA had a significantly effect on the main observation parameters. The 0.5 mg/L + IBA 0,5 mg/L treatment gives the best result at the number of shoots of 2.14 pieces and the best number of leaves of 2.44 strands. The BAP 0 + IBA 1 mg/L treatment gives the best result against the shoots height of 1.95 cm.